Increased miR‐195 aggravates neuropathic pain by inhibiting autophagy following peripheral nerve injury. Issue 4 (30th January 2013) - Shi, Guodong; Shi, Jiangang; Liu, Kun; Liu, Ning; Wang, Yuan; Fu, Zhiyi; Ding, Jiandong; Jia, Lianshun; Yuan, Wen
Abstract Following peripheral nerve injury (PNI) microglia proliferates and adopts inflammation that contributes to development and maintenance of neuropathic pain. miRNAs and autophagy are two important factors in the regulation of inflammation. However, little is known about whether miRNAs regulate neuroinflammation and neuropathic pain by controlling autophagy. In the study, we demonstrated that miR‐195 levels were markedly increased in rats subjected to L5 spinal nerve ligation (SNL). Upregulated miR‐195 was also found in spinal microglia of rats with SNL. The overexpression of miR‐195 contributed to lipopolysaccharide‐induced expression of proinflammatory cytokines IL‐1β, TNF‐α, and iNOS in cultured microglia. Upregulated miR‐195 also resulted in increased mechanical and cold hypersensitivity after PNI, whereas miR‐195 inhibition reduced mechanical and cold sensitivity. We further demonstrated that PNI significantly inhibited microglial autophagy activation, whereas miR‐195 inhibitor treatment increased autophagy activation and suppressed neuroinflammation in vivo and in vitro. More important, autophagy inhibition impaired miR‐195 inhibitor‐induced downregulation of neuroinflammation and neuropathic pain. Additionally, ATG14 was identified as the functional target of miR‐195. Conclusions: These data demonstrated that miR‐195/autophagy signaling represents a novel pathway regulating neuroinflammation and neuropathic pain, thus offering a new target for therapy of neuropathic pain.